Chapter 1 Migrant State Performance Report Data, 1991-92 - Westat, Inc., Rockville, MD.; Westat, Inc., Rockville, MD. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1994)
This report summarizes the participation and achievement information provided by state education agencies on the Chapter 1 Migrant Education Program (MEP) for 1991-92. The 1991-92 school year was marked by dramatic growth in the number of participants receiving MEP services in both regular and summer terms. In both terms, migrant participants were more likely to receive reading and mathematics than any other instructional service. Of the 531,841 participants reported as an unduplicated count of both terms, 80 percent were Hispanic and 11 percent were White, not Hispanic. Fifty-four percent were formerly migrant, 32 percent were currently migrant interstate, and 14 percent were currently migrant intrastate. Participation increased 22 percent from the previous year. Four percent of participants were disabled, and 20 percent were limited English proficient. States reported achievement data in basic and advanced reading and mathematics for students in grades 2-12 using various norm-referenced models (one point in time, two points in time, pretest/posttest, and sustained gain models). Federal funding for Chapter 1 MEP was approximately $294.6 million, a 4 percent increase from the previous year. The allocation per participant was $554. Extensive data tables detail information for the regular and summer terms on number and characteristics of migrant participants, services provided, full-time equivalent teachers and other staff, achievement results for basic and advanced reading and mathematics, and funding allocations by year and state. Appendices discuss program evaluation requirements, reporting problems, and methodology, and contain the data collection instrument and instructions. (SV)
Sponsoring Agency: Department of Education, Washington, DC. Office of the Under Secretary.
Contract Number: LC89015001.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Elementary Secondary Education; Enrollment; Federal Aid; Migrant Education; Preschool Education; State Programs; Student Characteristics; Tables (Data); Teachers; ECIA Chapter 1 Migrant Programs; Migrant Education Program -- Student Support Services; Reports, Evaluative; Numerical/Quantitative Data; Tests/Questionnaires.